ChemInform Abstract: Pillar[5]‐ and Pillar[6]arene‐Based Supramolecular Assemblies Built by Using their Cavity‐Size‐Dependent Host—Guest Interactions. Issue 26 (1st July 2014) - Ogoshi, T.; Yamagishi, T.
Abstract Review: 112 refs.